Pengaruh Kontrol Diri Terhadap Perilaku Konsumtif Mahasiswa Pendidikan Ekonomi 2022 Universitas Lampung - Wanty Nurkholifah; Selly Ismi Safitri; Indah Nur Aulia; Rahmawati; Pujiati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
commenced their studies in 2022, tend to exhibit an increase in consumptive behaviour. This trend appears to be influenced by the ease of purchasing goods through e-commerce platforms and the continuous exposure to promotional content on social media. The objective of this study is to determine the effect of self-control on the consumptive behaviour of Economic Education students from the 2022 cohort at the University of Lampung. This research adopts a quantitative approach, employing a descriptive-verificative method. The study utilises both an ex post facto and survey-based design. Data were collected through observation, interviews, and questionnaires. The total population consisted of 104 students, from which a sample of 83 respondents was selected using the Slovin formula. The sampling technique applied was probability sampling with a simple random sampling method. The data analysis process included normality and homogeneity tests, as well as classical assumption tests comprising linearity, multicollinearity, and heteroscedasticity assessments. A simple linear regression analysis was conducted for hypothesis testing. The results indicated that the calculated t-value (tcount) = 5.988 exceeded the critical value (ttable) = 1.989, with a significance level of 0.000, which is below the 0.05 threshold. These results demonstrate that self-control has a statistically significant effect on consumptive behaviour. The coefficient of determination (R²) was 0.307, suggesting that self-control accounts for 30.7% of the variation in consumptive behaviour.